Oral Microbiota, Its Equilibrium and Implications in the Pathophysiology of Human Diseases: A Systematic Review - Barbara Giordano-Kelhoffer; Cristina Lorca; Jaume March Llanes; Alberto Rábano; Teodoro del Ser; Aida Serra; Xavier Gallart-Palau (Biomedicines, 2022)
Imbalances of the oral microbiota and dysbiosis have traditionally been linked to the occurrence of teeth and oral diseases. However, recent findings indicate that this microbiota exerts relevant influence in systemic health. Dysbiosis of the oral microbiota is implicated in the apparition and progression of cardiovascular, neurodegenerative and other major human diseases. In fact, the oral microbiota are the second most diverse and largely populated microbiota of the human body and its relationships with systemic health, although widely explored, they still lack of proper integration. The purpose of this systematic review is thus to widely examine the implications of oral microbiota in oral, cardiovascular and neurodegenerative diseases to offer integrative and up-to-date interpretations. To achieve that aim, we identified a total of 121 studies curated in PUBMED from the time interval January 2003–April 2022, which after careful screening resulted in 79 studies included. The reviewed scientific literature provides plausible vias of implication of dysbiotic oral microbiota in systemic human diseases, and encourages further research to continue elucidating the highly relevant and still poorly understood implications of this niche microbiota in systemic health. PROSPERO Registration Number: CRD42022299692. This systematic review follows relevant PRISMA guidelines.